Comparison between Manual Lymph Drainage and Lymph stick on Circumference, Volume, Extracellular distribution ratio, Oxygen saturation, Body temperature and Satisfaction survey - Kim, Hyo-Jeong; Kim, Na-Young; Lee, Hye-Jeong; Lee, Dong-Yeop; Hong, Ji-Heon; Kim, Jin-Seop; Yu, Jae-Ho (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study investigated efficient interventional methods for reducing edema in women. Methods/Statistical analysis: 20 healthy adult women were participated in this study and directed to wear high heels. Then, three interventions were applied to them; long sitting, manual lymph drainage (MLD), lymph stick. This studymeasured the circumference, volume, extracellular distribution ratio, oxygen saturation, body temperature andsatisfaction survey. Comparisons between each intervention were analyzed through one-way ANOVA and intragroup comparisons were used by T-test.Findings: The control group (long sitting) showed no significant difference in edema reduction. However, MLD and lymph stick showed significant differences (p